ASPEK HUKUM CYBERCRIME TERHADAP MODUS SCAM PINJAMAN ONLINE BERBASIS ARTIFICIAL INTELLIGENCE - Rohmatul Karimah; Ahmad Irzal Fardiansyah; Fristia Berdian Tamza (INTELIGENSIA MEDIA, 2026)
The development of Artificial Intelligence (AI) has significantly impacted Indonesia’s digital finance sector. While AI enhances efficiency in online lending (fintech lending) services, it also introduces sophisticated financial scams. AI-driven online loan scams involve digital manipulation through deepfakes, chatbot phishing, and personal data misuse for illegal profit. This study aims to analyze the legal aspects of cybercrime in AI-based financial scams using a normative juridical approach, focusing on Law No. 11 of 2008 on Electronic Information and Transactions, Law No. 4 of 2023 on Financial Sector Development and Reinforcement, and Law No. 27 of 2022 on Personal Data Protection. The findings indicate that AI-driven loan scams represent a form of organized cybercrime that requires technology-based law enforcement. Legal reform and institutional collaboration between the Financial Services Authority (OJK), the Police, and the Ministry of Communication and Information are essential to implement Regulatory Technology (RegTech) as a preventive and control mechanism for AI-related scams.